Penggunaan Tanda Baca Koma (,) dalam Tajuk Rencana Pada Siswa di Sekolah Menengah Atas - Supriyadin Supriyadin (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya, 2021)
The objectives of this study were: (1) Obtaining data regarding the ability of Class XI students of SMAN 1 Cikijing in using punctuation marks (,) in the editorial. (2) Obtain data regarding errors using a comma (,) in the header. The hypothesis proposed in this study is the Analysis of Misuse of Comma (,) Punctuation in the Editorial for Class XI Students of SMA Negeri 1 Cikijing for the 2014/2015 academic year. So in this study, the authors formulated a hypothesis, namely: